Use of Strychnos nux-vomica (Azraqi) seeds in Unani system of medicine: role of detoxification - Masood, Akbar; Akbar, Seema; khan, Shamshad ahmad (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Some plants used in Unani system of medicine are toxic, even deadly poison. The drugs having such plants as their components are detoxified before they are dispensed to the patients. One such drug, capsule Hudar, has Strychnos nux-vomica L. (Azraqi) seeds as one of its components and is very effectively used to elevate blood pressure. Ancient manuscripts describe many methods of its detoxification. It has been found that the detoxification processes studied reduce the strychnine amount, as determined either by using uv-vis spectrophotometer or HPLC, present in Strychnos nux vomica seeds which is responsible for Strychnos nux vomica toxicity. The decrease in strychnine amount was maximum when the seeds were immersed for detoxification in excess of water for 5 days, in milk for 2 days followed by their boiling in milk. Strychnine in small amounts has been reported to give subjective feeling of stimulation